Effects of ventricular conduction block patterns on mortality in hospitalized patients with dilated cardiomyopathy: a single-center cohort study. Issue 1 (December 2016) - Li, Xiaoping; Luo, Rong; Fang, Wei; Xu, Xiaolei; Niu, Guodong; Xu, Yixian; Fu, Michael; Hua, Wei; Wu, Xiushan
Abstract Background Ventricular conduction blocks (VCBs) are associated with poor outcomes in patients with known cardiac diseases. However, the prognostic implications of VCB patterns in dilated cardiomyopathy (DCM) patients need to be evaluated. The purpose of this study was to determine all-cause mortality in patients with DCM and VCB. Methods This cohort study included 1119 DCM patients with a median follow-up of 34.3 (19.5–60.8) months, patients were then divided into left bundle branch block (LBBB), right bundle branch block (RBBB), intraventricular conduction delays (IVCD) and narrow QRS groups. The all-cause mortality was assessed using Kaplan-Meier survival curves and Cox regression. Results Of those 1119 patients, the all-cause mortality rates were highest in patients with IVCD (47.8, n  = 32), intermediate in those with RBBB (32.9, n  = 27) and LBBB (27.1 %, n  = 60), and lowest in those with narrow QRS (19.9 %, n  = 149). The all-cause mortality risk was significantly different between the VCB and narrow QRS group (log-rankχ 2 = 51.564, P  < 0.001). The presence of RBBB, IVCD, PASP ≥ 40 mmHg, left atrium diameter and NYHA functional class were independent predictors of all-cause mortality in DCM patients. Conclusions Our findings indicate that RBBB and IVCD at admission, but not LBBB, were independent predictors of all-cause mortality in patients with DCM.